2017
DOI: 10.4274/tjh.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Retrospective Analysis of Turkish Patients with Chronic Myeloproliferative Neoplasms

Abstract: Objective:Chronic myeloproliferative neoplasms (CMPNs) that include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) are Philadelphia-negative malignancies characterized by a clonal proliferation of one or several lineages. The aim of this report was to determine the demographic features, disease characteristics, treatment strategies, and survival rates of patients with CMPNs in Turkey.Materials and Methods:Across all of Turkey, 9 centers were enrolled in the study. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
5
13
1
Order By: Relevance
“…The results demostrated that leukemic and fibrotic transformations occurred at rates of 0.6% and 13.2. 21 The rates of leukemic and fibrotic transformation were similar to those of our study. Frederiksen et al showed that the patients with different CMPD were at increased risk of developing both additional hematologic and non-hematologic malignancies.…”
Section: Discussionsupporting
confidence: 89%
“…The results demostrated that leukemic and fibrotic transformations occurred at rates of 0.6% and 13.2. 21 The rates of leukemic and fibrotic transformation were similar to those of our study. Frederiksen et al showed that the patients with different CMPD were at increased risk of developing both additional hematologic and non-hematologic malignancies.…”
Section: Discussionsupporting
confidence: 89%
“…Hemorrhages due to treatment (antiplatelet and anticoagulant drugs, thrombocytopenia secondary to HU), disease evolution or complications (thrombocytopenia resulting from disease transformation or splanchnic thrombosis and/or extramedullary hematopoiesis-related portal hypertension/hypersplenism, coagulopathy of liver failure caused by BCS, etc. ), acquired von Willebrand syndrome (AVWS), and intrinsic platelet dysfunctions are also possible during the disease course (51). Diagnosis and management of these specific scenarios involve some specific details.…”
Section: Specific Recommendationsmentioning
confidence: 99%
“…In ET, PV and PMF are BCR/ABL-negative CMPDs. The effects of a few genetic mutations have been reported recently in BCR/ABL-negative CMPDs (2).…”
Section: Introductionmentioning
confidence: 98%
“…In ET, typical increases in megakaryocyte and platelet counts are observed. In idiopathic myelofibrosis, bone marrow fibrosis is more prominent (2). In ET, PV and PMF are BCR/ABL-negative CMPDs.…”
Section: Introductionmentioning
confidence: 99%